Polymorphic variants of the oxytocin receptor gene (OXTR rs53576) and psychosocial characteristics in adolescent - K. V. Afonicheva; M. V. Smolnikova; M. V. Shubina; S. Yu. Tereshchenko (Сибирский научный медицинский журнал, 2024)
Adolescence is one of the most difficult period in the person’s life. Adolescent behavior is influenced by many factors, including the social environment, internal attitudes and hormonal levels. One of the important hormones that can change behavior is oxytocin – an extremely important prosocial neuropeptide that influences social bonding from an early age. The effect of oxytocin on the psycho-emotional state is quite individual and may depend on age, gender, ethnocultural factors, social environment, the presence of stress factors, and personality traits. The results of the studies indicate the relationship between the increased concentration of oxytocin and the presence of developed social contacts. The aim of this work was to identify an association between psychosocial characteristics in adolescent of different gender and rs53576 polymorphism of the oxytocin receptor gene. Material and methods. Psychological and genetic testing of adolescents aged 11–18 living in the territory of the Angara-Yenisei macroregion was carried out. Mental health assessment was carried out using the Russian version of the questionnaire “Strengths and difficulties” by R. Goodman. Results and discussion. The rs53576 OXTR AA genotype is more frequent in boys than in girls (20.8 % vs. 14.3 %, p = 0.03). The association of the rs53576 OXTR A allele with social behavior disorders and depression was previously shown. Boys carrying the AA genotype have significantly higher scores (borderline values) on the scales of “Emotional symptoms” and “Problems communicating with peers” compared with carriers of the GA and GG genotypes. Conclusions. Evidences of differing individual psychosocial consequences of high activity of the oxytocinergic system, depending on the context of the social environment, allowed us to formulate the “hypothesis of the social significance of oxytocin”. Problems in communication with peers in adolescents with pronounced social empathy and altruistic personal characteristics can be successfully overcome. Both the general orientation of the pedagogical process towards the approval of prosocial behavior, and socially significant personalities, whom adolescents can perceive as an example to follow, can help in many ways.